2017
DOI: 10.1121/1.5007952
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glottal closure on the phonatory process in ex vivo porcine larynges

Abstract: Many cases of disturbed voice signals can be attributed to incomplete glottal closure, vocal fold oscillation asymmetries, and aperiodicity. Often these phenomena occur simultaneously and interact with each other, making a systematic, isolated investigation challenging. Therefore, ex vivo porcine experiments were performed which enable direct control of glottal configurations. Different pre-phonatory glottal gap sizes, adduction levels, and flow rates were adjusted. The resulting glottal closure types were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 54 publications
4
21
0
Order By: Relevance
“…Compared to the data of Döllinger et al [39] the value of R B for GGI 3 in this study was 42% higher; see Table 7. For GGI 1-2 our findings support other studies that higher energy transfer R B from the glottal flow to vocal folds yields an improved acoustic quality (i.e., higher CPP values) [39,60,65]. Surprisingly, we found contrary results for GGI 2-3 , that R B was increasing/improving while CPP decreased/deteriorated even further; see Table 5.…”
Section: Aerodynamic Parameterssupporting
confidence: 85%
See 1 more Smart Citation
“…Compared to the data of Döllinger et al [39] the value of R B for GGI 3 in this study was 42% higher; see Table 7. For GGI 1-2 our findings support other studies that higher energy transfer R B from the glottal flow to vocal folds yields an improved acoustic quality (i.e., higher CPP values) [39,60,65]. Surprisingly, we found contrary results for GGI 2-3 , that R B was increasing/improving while CPP decreased/deteriorated even further; see Table 5.…”
Section: Aerodynamic Parameterssupporting
confidence: 85%
“…Also, similar findings were reported by Wolfe et al [59] who found a correlation between jitter and the degree of dysphonia by considering the mean fundamental frequency. Hence, an increased fundamental frequency may be seen as an indicator of a pathological or disordered voice [60]. Air flow strength here (120 mL/s) is close to the value of Döllinger et al [39] of 117 mL/s, which was to be expected since the data were collected during the same series of experiments.…”
Section: Fundamental Phonatory Parameterssupporting
confidence: 83%
“…(3) Two rods were symmetrically tightened posteriorly, simulating the adduction process, to bring the larynx in phonatory position, i.e., until the glottis was entirely closed. Then the phonatory threshold pressure (PTP) level was determined by manually and continuously increasing the air flow through the larynx until sustained phonation occurred (Birk et al, 2017b), i.e., PTP was determined as the subglottal pressure level at which the vocal folds initiated sustained vibration. From the PTP, the airflow was increased 14 times successively in steps of 0.5 lm À1 (8.33 mls À1 ).…”
Section: Experimental Procedures For Phonationmentioning
confidence: 99%
“…In the 2D view from above, the vocal folds move medially toward each other, giving the impression of a complete closure of the glottis . Because they are on a different level, they allow too much air to pass through the glottis, causing alterations of the normal vocal fold vibration cycle and dysphonia . In this case, the evaluation of the closing and closure process, as well as the determination of symmetry between the left and right vocal fold, would be important.…”
Section: Discussionmentioning
confidence: 99%
“…38 Because they are on a different level, they allow too much air to pass through the glottis, causing alterations of the normal vocal fold vibration cycle and dysphonia. 39,40 In this case, the evaluation of the closing and closure process, as well as the determination of symmetry between the left and right vocal fold, would be important. As assumed, the newly invented 3D imaging system can visualize such information.…”
Section: Discussionmentioning
confidence: 99%